Epidemiology of Taenia saginata taeniosis/cysticercosis: a systematic review of the distribution in the Americas - Uffe Christian Braae; Lian F. Thomas; Lucy J. Robertson; Veronique Dermauw; Pierre Dorny; Arve Lee Willingham; Anastasios Saratsis; Brecht Devleesschauwer (Parasites & Vectors, 2018)
Abstract Background The distribution of Taenia saginata in the Americas is unclear. Establishing the distribution, economic burden, and potentials for control of bovine cysticercosis is increasingly important due to the growing demand for beef. This paper aims to take the first step and reviews the recent distribution of T. saginata taeniosis and bovine cysticercosis on a national level within the Americas. Methods We undertook a systematic review of published and grey literature for information on the occurrence, prevalence, and geographical distribution of bovine cysticercosis and human taeniosis in the 54 countries and territories of the Americas between January 1st, 1990 and December 31st, 2017. Data on bovine cysticercosis from OIE reports from 1994 to 2005 were also included. Results We identified 66 papers from the Americas with data on the occurrence of taeniosis or bovine cysticercosis and an additional 19 OIE country reports on bovine cysticercosis. Taeniosis was reported from 13 countries, with nine of these countries reporting specifically T. saginata taeniosis, and four countries reporting non-species specific taeniosis. The reported prevalence of taeniosis ranged between 0.04–8.8%. Bovine cysticercosis was reported from 19 countries, nine identified through the literature search, and an additional 10 identified through the OIE country reports for notifiable diseases. The reported prevalence of bovine cysticercosis ranged between 0.1–19%. Disease occurrence was restricted to 21 countries within the Americas, the majority from the mainland, with the only island nations reporting either bovine cysticercosis or taeniosis being Cuba, Haiti, and the US Virgin Islands. Conclusions Taenia saginata is widely distributed across 21 of the 54 countries in the Americas, but insufficient epidemiological data are available to estimate the subnational spatial distribution, prevalence, incidence and intensity of infections. This needs to be addressed through active surveillance and disease detection programmes. Such programmes would improve the data quantity and quality, and may enable estimation of the economic burden due to bovine cysticercosis in the region in turn determining the requirement for and cost-effectiveness of control measures.